Effect of the fetilization on the pasture Brachíaria híbrido CV CIAT BR02/1794 as measure of mitigation to climate change - Mejia-Castillo, Harin Joel; Nájera Aparicio, Kenny; Rubi, Rober Danilo; Ramirez, Carmen Nataly (Ibero-american JournalL of Bioeconomy and Climate Change e-ISSN 2410-7980, 2018)
The effect of different levels of fertilization (0, 50, 100 and 150 KgHa-1) on the yield and nutritional composition in the cobra grass (Brachíaria hibrido cv CIAT BR02 / 1794) was evaluated. Four treatments with four repetitions were evaluated, using an experimental design in completely randomized blocks. The evaluated variables were Performance KgHa-1, Dry Matter, Raw Protein and Fiber. It was found that the variables responded favorably to the dose of 100 KgHa-1 giving the following results, for KgHa-1 Performance: 5,170.46 at 30 days, Crude protein: 14.43% at 30 days, FDA: 31.37% at 30 days . With the data obtained in the study, it is shown that the nitrogen fertilization has an effect on the yield and nutritional composition on the hybrid Brachiaria cv CIAT BR02 / 1794 grass, and the level of fertilization with the highest benefit / cost ratio (1.40 Lps) ) was 100 KgHa-1.